Frequency of Epidermal Growth Factor Receptor Gene Variant in Roma Population - Mačeková, Soňa; Mathia, Matúš; Dojčáková, Dana (Genetic testing and molecular biomarkers, 2023)
Aims: The pathogenic variant, p.GLY428Asp (c.1283G-A), in the epidermal growth factor receptor (EGFR) gene causes neonatal inflammatory skin and bowel disease 2, a disorder that is lethal during infancy due to skin infections and sepsis. This variant seems to be restricted to people of Roma origin with the majority of patients thus far reported being from Slovakia or the Czech Republic. The aim of this study was to establish the frequency of this variant in the Roma population in Slovakia. Methods: A population sample of 1321 unrelated healthy individuals of Roma origin from Slovakia was tested for the p.GLY428Asp variant in EGFR gene by real-time PCR. Results: The carrier frequency in the Roma ethnic group was 2.65%. Conclusions: This is the first report of the frequency of this variant. A high frequency of carriers together with a significant number of patients reported previously proves the p.GLY428Asp variant in the EGFR gene is a major health concern of the Roma populations in Slovakia and neighboring regions.
Keywords: Infant, Newborn; Roma; Humans; carrier testing; sepse; Sepsis; Gypsies; NISBD2; Real-Time Polymerase Chain Reaction; kvantitativní polymerázová řetězová reakce; lidé; Czech Republic; Česká republika; novorozenec; geny erbB-1; Romové; Genes, erbB-1; EGFR gene